KETERAMPILAN, PENGETAHUAN DAN KOMUNIKASI TERHADAP PRODUKTIVITAS KERJA PEGAWAI KIP KABUPATEN BIREUEN - Mutia Nanda; Ibrahim Ibrahim (LPPM-UNIKI, 2026)
Work productivity is a goal of all organizations, and this is largely related to the internal factors of its employees. Therefore, this study aims to examine the contribution of employee skills, knowledge, and communication factors. The study was conducted on 45 employees at the Independent Election Commission (KIP) of Bireuen Regency. The results found: (1) employee skills have a significant direct and indirect influence through knowledge and communication, amounting to 53.97%. (2) knowledge has a direct and indirect effect through skills and communication on work productivity, amounting to 57%. (3) communication also has a direct and indirect influence through skills and knowledge, amounting to 63.14%. (4) There is a fairly strong causal relationship between skills, knowledge, and communication, so that simultaneously, skills, knowledge, and communication contribute to work productivity by 78,6%.